Competition, regulation, and broadband access to the internet - Georg Götz (Philipps-University Marburg, Faculty of Business Administration and Economics, 2009)
This paper reexamines the effect of the regulatory regime on both penetration and coverage of broadband access to the internet. The framework also allows for an evaluation of different public policy measures such as subsidization of broadband demand and supply. A welfare analysis asks what the optimal regulatory regime is and whether and how high-speed access to the internet should be subsidized. Using an approach similar to Valletti et al. (2002), the paper highlights the importance of population density for whether firms invest to provide internet access. The analysis reveals a trade-off between coverage and penetration
Keywords: 330